2015
DOI: 10.14737/journal.jahp/2015/3.4.82.87
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucellosis in Holstein-Friesian and Indigenous Cattle Breeds of Sindh Province, Pakistan

Abstract: | Brucellosis is considered to be one of the most widespread zoonosis in the world. A comparative study on the seroprevalence of brucellosis in indigenous cattle breeds and exotic cattle (Holstein-Friesian) was carried out in district Hyderabad, Sindh, Pakistan. A total of 500 serum samples, 100 each from Red Sindhi, Thari, Kankrej, Bhagnari and Holstein-Friesian breeds were collected from both male and female animals and examined by Rose Bengal plate test (RBPT), serum agglutination test (SAT) and Competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Whereas in present study the prevalence was recorded higher (52.63%) in right quarters as compared to left side quarters (47.36%). This inconsistency in results could be due to the breed differences (Mangi et al, 2015), as in present study dairy goats of different breeds were examined for prevalence of subclinical mastitis.…”
Section: Prevalence Of Subclinical Mastitis In Dairy Goats Analysed Bmentioning
confidence: 84%
“…Whereas in present study the prevalence was recorded higher (52.63%) in right quarters as compared to left side quarters (47.36%). This inconsistency in results could be due to the breed differences (Mangi et al, 2015), as in present study dairy goats of different breeds were examined for prevalence of subclinical mastitis.…”
Section: Prevalence Of Subclinical Mastitis In Dairy Goats Analysed Bmentioning
confidence: 84%
“…(Hussin et al, 2016;Peter et al, 2015). Moreover, it has been revealed that different species/breeds have different susceptibility/resistant levels for bacterial pathogens (Mangi et al, 2015). A higher prevalence in Hyderabad district could be due to that it is a most populous city of Sindh province after Karachi and also a border city where animals brought from several neighboring animal markets for sell .…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the reports of Pirzada et al (2016) in Pakistan who reported 52.63% prevalence for the right udder halves and 47.36% for the left udder halves. This was thought to be due to the greater milk production capacity of the right udder halves (Mangi et al 2015). Staphylococcus aureus has been known to show multiple antimicrobial resistance patterns.…”
Section: Resultsmentioning
confidence: 99%